Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Yang Terdaftar Di BEI - Verani Meika, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is to empirically examine the influence of capital structure, firm size, assets tangibility, dividend policy, and managerial ownership on firm value. This research uses secondary data. Technique used to select the sample is purposive sampling. Subjects of this research are manufacturing company listed in Indonesian Stock Exchange for period 2015 – 2017. There are 18 manufacturing companies that meet the criteria as a sample. Data analysis technique uses E-views version 9.0. Results showed that assets tangibility, dividend policy, and managerial ownership insignificantly influence firm value. On the other hand, capital structure negative and significantly influence firm value, meanwhile firm size positive and significantly influence firm value